The official Cambridge guide to IELTS : for academic & general training : student's book with answers - Cullen, Pauline; French, Amanda; Jakeman, Vanessa (Cambridge : Cambridge University Press, 2014)
'The official Cambridge guide to IELTS' is THE definitive guide to IELTS. It contains all you need to succeed in the exam. Skill-building exercises cover all of the question types in the exam for both the General Training and Academic modules. Our research into real IELTS candidates' exam answers - and the mistakes they make, helps you avoid the same ones! Eight official practice tests and a focus on test-taking strategy help you maximise your score. The DVD-ROM includes videos of the Speaking test, and all the listening material, including the tests, as MP3 files.
Book is accompanied by one DVD-ROM'The official Cambridge guide to IELTS' bearing the same call number and available at Koleksi Media, Perpustakaan PPUKM.
Book is accompanied by 1 CD entitled'The official Cambridge guide to IELTS' bearing the same call number and available at Koleksi Media.
Keywords: International English Language Testing System -- Study guides; English language -- Problems, exercises, etc